Radiation monitoring of locality in real-time mode by fibre-optical dosimetr - GetmanetsO. М.; Gordienko, V. G.; DrozdovА. А.; Phelikhatiy, N. M. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
The method of duration remote radiation monitoring of locality by fibre-optical dosimeter with the additional point sensor of radiation, which allows quickly and reliably to determine the field of radiation background into the controlled area and near-by its border and also to localize the sources of the promoted radiation has been proposed.